Phillips 66: possibility of a pedagogical intervention (Research, Society and Development, 2019)
This experience report aims to reflect the application of a Phillips 66 Teaching Strategy with fifteen high school students from a Taquari Valley State School, Rio Grande do Sul. This is a qualitative research and was based theoretically on the theoretical presuppositions of Mathematical Research, recommended by Ponte, Brocado and Oliveira (2009). It can be evidenced that through it it was possible to challenge the students to the numerous actions: the defense of ideas, the power of argumentation, the judgment and the decision making. According to the students' reports, it was possible to perceive that they are accustomed to routine activities in the classroom and emphasize that the strategy was a rich form of exchange of dialogues, discussions and debate, supported in a real situation.